2011
DOI: 10.1007/s12588-011-9001-5
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun PVDF/BaTiO3 nanocomposites: polymorphism and thermal emissivity studies

Abstract: Non-woven fiber mats of PVDF/BaTiO 3 nanocomposites were prepared by electrospinning and characterized by various techniques. Scanning electron micrographs show that fibers obtained were randomly oriented with fiber diameters ranging between 200 nm and 400 nm. The structure of the nanocomposite fibers was studied using X-ray diffraction and ATR-FTIR techniques. The PVDF electrospun mats exhibited a mixed crystalline phase consisting of α and β phases. However the addition of BaTiO 3 was found to result in sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 18 publications
(18 reference statements)
1
22
0
1
Order By: Relevance
“…The average fiber diameter was in accordance with different previously reported studies [29,35]. The co-solvent system used (DMF and acetone) was selected according to previously reported works [29,36,37]. Basing on a study of Yee et al [37], which reported that an increase of DMF/acetone ratio induced a decrease in fiber diameter and an increase of beads present on the electrospun mesh, the 1:1 DMF/acetone ratio was selected for conducting our experiments.…”
Section: Production Morphology and Topography Of Btnp/pvdf Fibersmentioning
confidence: 82%
See 2 more Smart Citations
“…The average fiber diameter was in accordance with different previously reported studies [29,35]. The co-solvent system used (DMF and acetone) was selected according to previously reported works [29,36,37]. Basing on a study of Yee et al [37], which reported that an increase of DMF/acetone ratio induced a decrease in fiber diameter and an increase of beads present on the electrospun mesh, the 1:1 DMF/acetone ratio was selected for conducting our experiments.…”
Section: Production Morphology and Topography Of Btnp/pvdf Fibersmentioning
confidence: 82%
“…The obtained fiber diameters decreased with the increase of the collector V t , although differences between datasets were not statistically significant ( also induced a reduction (not statistically significant) of the fiber diameter obtained for the composite fibers. The average fiber diameter was in accordance with different previously reported studies [29,35]. The co-solvent system used (DMF and acetone) was selected according to previously reported works [29,36,37].…”
Section: Production Morphology and Topography Of Btnp/pvdf Fibersmentioning
confidence: 87%
See 1 more Smart Citation
“…7, the peaks at 613, 762 and 975 cm À1 are for a phase of the PVDF. 37 Further, the peaks at 841 and 1280 cm À1 are attributed to b phase of PVDF. 37 The peaks at 613 and 762 cm À1 are because of CF 2 and skeletal bending of C (F)-C (H)-C (F) of a phase of the PVDF, while the peak at 975 cm À1 is due to CH 2 bending mode of a phase.…”
Section: Fourier Transform Infrared Spectroscopy (Ftir) Analysismentioning
confidence: 96%
“…Other electrospun PVDF/BT nanofiber webs were reported by Chunmal et al with DMF/acetone solvent [ 105 ]. FTIR investigations illustrated that the obtained samples of PVDF and PVDF/BT both have α- and β-phases of PVDF.…”
Section: Additives To Improve Piezoelectric Properties Of Electrosmentioning
confidence: 99%